2022
DOI: 10.3390/rs14143365
|View full text |Cite
|
Sign up to set email alerts
|

Turning the Tide on Mapping Marginal Mangroves with Multi-Dimensional Space–Time Remote Sensing

Abstract: Mangroves are a globally important ecosystem experiencing significant anthropogenic and climate impacts. Two subtypes of mangrove are particularly vulnerable to climate-induced impacts (1): tidally submerged forests and (2) those that occur in arid and semi-arid regions. These mangroves are either susceptible to sea level rise or occur in conditions close to their physiological limits of temperature and freshwater availability. The spatial extent and impacts on these mangroves are poorly documented, because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Some structural and environmental constraints affect the detectability of mangroves with remote sensing models. For example, the sparse canopy and short stature of mangroves relative to other trees cause their limited visibility ( Hickey and Radford 2022 ). The mangroves in SBPS form narrow fringes and small patches of stands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some structural and environmental constraints affect the detectability of mangroves with remote sensing models. For example, the sparse canopy and short stature of mangroves relative to other trees cause their limited visibility ( Hickey and Radford 2022 ). The mangroves in SBPS form narrow fringes and small patches of stands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of topography was reduced, and the spectral differences across bands were enhanced using the band ratio [15]. While GCVI was employed, several studies showed that mapping mangrove chlorophyll and GCVI had an excellent correlation [16]. This formula is expressed in equation 1-7.…”
Section: Study Locationmentioning
confidence: 99%
“…Spectral indices provide valuable information about the environment. In mangroves, key indices are those that offer information about green vegetation (Red and near-infrared) and water reflectance (Green and middle infrared) [16]. Integrating characteristics of water and vegetation can help differentiate between land vegetation and mangrove vegetation [20].…”
Section: Feature Engineeringmentioning
confidence: 99%
“…Integrating characteristics of water and vegetation can help differentiate between land vegetation and mangrove vegetation [20]. Hickey and Radford (2022) discovered that the Modified Normalized Water Index (MNDWI) and Green Chlorophyll Vegetation Index (GCVI) in Landsat-8 imagery are the best predictors for mangroves [16], Meanwhile, in Sentinel-2 imagery, it was discovered that MNDWI and Mangrove Discrimination Index (MDI) significantly enhance mangrove extraction performance [20]. Other relevant spectral indices for mangrove classification include the Normalized Difference Moisture Index (NDMI) [13], Normalized Difference Soil Index (NDSI) [17], and Mangrove Vegetation Index (MVI) [31].…”
Section: Feature Engineeringmentioning
confidence: 99%
See 1 more Smart Citation